Embedding inulin fructotransferase from Arthrobacter aurescens into novel curdlan-based mesoporous silica microspheres for efficient production of Difructose Anhydride III. (30th November 2019) - Liu, Xia; Qi, Xianghui; Zhu, Song; Jiang, Bo; Gao, Song; Zhang, Yifeng; Wang, Hongling; Xu, Shumin; Liu, Yifei; An, Yingfeng
Highlights: Inulin fructotransferase was embedded in curdlan-based mesoporous silica microspheres. Curdlan with special properties was used to improve characteristics of microspheres. Both free and immobilized Aa-IFTase were stable with the presence of organic solvents. The resulting CMSiM-Aa-IFTase showed significantly improved enzymic characteristics. Abstract: A novel strategy was used to produce inulin fructotransferase from Arthrobacter aurescens (Aa-IFTase) embedded in curdlan-based mesoporous silica microspheres (CMSiM-Aa-IFTase). The CMSiM-Aa-IFTase was constructed by co-entrapping cross-linked Aa-IFTase aggregates and curdlan into biomemitic silica, and the curdlan was subsequently removed by digestion with endo -β-1, 3-glucanase. During this process, the curdlan served as an agent to introduce pores in silica microspheres. The resulting CMSiM-Aa-IFTase showed higher stability and activity than free Aa-IFTase and mCLEAs-Aa-IFTase (modified cross-linked enzyme aggregates with Aa-IFTase). Furthermore, the CMSiM-Aa-IFTase displayed good reusability and excellent storage stability. The excellent catalytic performances were due to the combinational structure from the cross-linked enzyme aggregates and hard shell of mesoporous silica microspheres, which might decrease the negative interaction between support and enzyme, and improve the mechanical properties. The CMSiM-Aa-IFTase was applicable for efficient production of Difructose Anhydride III (DFA III), and this approach should be highly valuable for preparing various mesoporous composites for catalysis.